Hydrophobic cement-based materials with micro-nano hierarchical structures: preparation, characterization, and stability assessment - Bian, Xiaolei; Yao, Wu; Liao, Gang; Liang, Guangwei; She, Anming; Wei, Yongqi (Frontiers in Materials, 2024)
With the increasing demand for durable and sustainable building materials, the development of superhydrophobic cement-based materials has gained significant attention. In this study, superhydrophobic cement-based materials with layered structures were fabricated. By replicating microstructures from sandpaper and applying nanoparticles and low-surface-energy materials, we achieved a water contact angle of 155.7°. The resulting material demonstrates excellent waterproof performance, low adhesion forces, and high resistance to damage, providing valuable insights for the development of durable, waterproof building materials for sustainable construction.